El crecimiento económico y su impacto en el medio ambiente a nivel mundial en el periodo 1990-2018 - Sandoval Analuisa, Nick Aldair (2023)
The environmental pollution is a problem that has persisted over time causing economic, social, and health problems since 60% of the ecosystems have been degraded. In this sense, the present research aims to analyze the incidence of economic growth on environmental pollution and other possible causes of this phenomenon worldwide, in the period 1990-2018. The information was compiled from the databases of the World Bank [WB] (2020) and the Globalization Index [KOF] (2020). Therefore, a Generalized Least Squares (GLS) model, the Westerlund's (2007) cointegration test, and the Dimietry and Hurlin's (2012) causality test were estimated. The results show that: economic growth has a positive relationship with CO2 emissions; imports of goods and services present a negative relationship with CO2 emissions; and it was determined that there is a long term relationship between economic growth, globalization index, gross capital strength and agricultural land and CO2 emissions. Furthermore, it was found that there is a bidirectional relationship, going from CO2 emissions to economic growth and vice versa. Consequently, the economic policy implication derived from our research is that public policies should promote increased spending on research and development in all sectors to combat environmental degradation and promote sustainable growth and development.